2004
DOI: 10.1002/pola.20129
|View full text |Cite
|
Sign up to set email alerts
|

Physically controlled, free‐radical polymerization of vaporized fluoromonomer on solid surfaces

Abstract: Gas/vapor-deposition polymerization (GDP) of vinyl monomer is expected to exhibit a unique polymerization behavior different from its polymerization in the liquid phase. Free-radical GDP of 2,2,3,3,3-pentafluoropropyl methacrylate (FMA) was carried out with a conventional free-radical initiator (azobisisobutyronitrile) on substrate surfaces. A linear relationship between the number-average molecular weight and polymer yield was observed, and the consecutive copolymerization of methyl methacrylate (MMA) and FMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Endo and coworkers reported physically controlled radical polymerization of vapor-phase vinyl monomers by conventional free-radical initiators deposited onto solid surfaces, such as aluminum plate. [76][77][78][79] Deposition polymerization in monomer vapor of MMA and styrene was initiated from free radicals on the surface and high molecular weight polymers formed on the substrate surfaces. During polymerization, the number-average molecular weight was found to increase linearly with polymer yield.…”
Section: Discussionmentioning
confidence: 99%
“…Endo and coworkers reported physically controlled radical polymerization of vapor-phase vinyl monomers by conventional free-radical initiators deposited onto solid surfaces, such as aluminum plate. [76][77][78][79] Deposition polymerization in monomer vapor of MMA and styrene was initiated from free radicals on the surface and high molecular weight polymers formed on the substrate surfaces. During polymerization, the number-average molecular weight was found to increase linearly with polymer yield.…”
Section: Discussionmentioning
confidence: 99%
“…10 Thus, this acceleration must be caused by factors such as an increase in the adsorption and absorption area of monomer molecules and the suppression of termination reactions caused by the isolation of active chain ends on the top surface of deposits, as reported previously. 11 Multimodal profiles with wide polydispersity values are typical profiles of the photo-VASP products obtained in this study. In spite of the multimodal profiles, the molecular weight tended to increase monotonously with the reaction time and polymer yield, demonstrating continuous propagation characteristics in photo-VASP.…”
Section: Resultsmentioning
confidence: 99%
“…5-9 Previously, we reported physically controlled living radical polymerization using free radical initiators by the VASP method, enabling the preparation of block copolymers, 10 the design of fine patterns, application to surface coatings with a fluorinated polymer 11 and the development of a homogeneous coating of a fine Fe-powder surface. 12 In these studies, a small amount of organic solvent was used to precoat initiators on substrate surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into consideration the previous results of GASP, [12][13][14]16 the molecular weight and PDI value of obtained polymers are considered to be affected by various factors, which include not only the composition ratio of the initiator system, but also the homogeneity of substrate/deposit surfaces. In the previous report, 12 it was found that the deposition rate of PMMA increased with reaction time, suggesting the enhancement of the polymerization by the increase in surface roughness.…”
Section: Gasp Of Mma With Various Feed Ratios Of Fe(0)/tsclmentioning
confidence: 99%
“…1), as described in previous reports. [12][13][14] A solution of TsCl (22 mg, 0.13 mmol) in diethyl ether (0.5 mL) and Fe(0) powder (50 mg) was added in a glass pan (bottom surface area, 154 mm 2 ; height, 40 mm). The glass pan was dried for 1 h at ambient temperature and then set in one of the bottom legs of the H-shaped glass tube reactor.…”
Section: General Procedures Of Gaspmentioning
confidence: 99%